Printable Organic Semiconductors for Radiation Detection: From Fundamentals to Fabrication and Functionality - Griffith, Matthew J.; Cottam, Sophie; Stamenkovic, Joshua; Posar, Jessie A.; Petasecca, Marco (Frontiers in Physics, 2020)
The deployment of organic semiconducting materials for radiation detection is an emerging and highly attractive area of materials science research. These organic materials offer the enticing vision of technologies created from low-cost materials that can be printed on-demand with a range of different tailored optoelectronic functionalities. An explosion in the number of available materials, improved functionality of materials, and sophistication of solution-based device fabrication techniques for organic semiconductors in recent years have led to considerable opportunities for the utilization of organic materials in the detection of ionizing radiation. While the potential of organic semiconducting materials for low-cost radiation detection is clear, transitioning these printable materials to a commercial reality presents a significant scientific challenge. In this work, we provide a comprehensive analysis of the use of organic semiconductors for radiation detection. We discuss the fundamental physics of these materials and how their conduction mechanisms, including charge generation and charge transport, differ significantly from established inorganic semiconductors. Various strategies employed to control the nanostructure in organic semiconductors to optimize charge generation and transport for radiation detection are discussed. We provide insights into the strategies employed to fabricate organic semiconducting devices at industrially relevant scales using roll-to-roll solution processing and finally discuss existing examples of organic semiconducting materials utilized in the radiation detection arena.